The Cakery Bakery / Nur Izzi Idris and Nur Alia Farhana A.Rahman - Idris, Nur Izzi; A.Rahman, Nur Alia Farhana (2022)
The Cakery is a company that sells cakes. The ‘Cakery’ refers to the cake name itself so that customers know the types of products that we sell. The owners of this company are Nur Izzi binti Idris and Nur Alia Farhana binti A.Rahman. The reason why we want to sell cake is that people like to eat cake as it has a delicious flavor that can make it a perfect companion for any cuisine. We target people of any age which include kids, teenagers, and adults. As we all know, the cake is served mainly during a birthday and as a part of the celebration. In The Cakery, we want to focus on three types of cake which are Lotus Biscoff Cheesecake, Chocolate Moist Cake, and Red Velvet Cake. This is because based on our view, this cake received a high demand among people. The Cakery consists of four workers which are Nur Izzi binti Idris and Nur Alia Farhana binti A.Rahman who are also the owners and two staff. We have created a Facebook Page in order to expand our business through social media sites and seek to learn how to post business products through Facebook whether teaser, hard sell, or soft sell post.